2021
DOI: 10.1016/j.tree.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Linking ecomechanical models and functional traits to understand phenotypic diversity

Abstract: Physical principles and laws determine the set of possible organismal phenotypes. Constraints arising from development, the environment, and evolutionary history then yield workable, integrated phenotypes. We propose a theoretical and practical framework that considers the role of changing environments. This 'ecomechanical approach' integrates functional organismal traits with the ecological variables. This approach informs our ability to predict species shifts in survival and distribution and provides critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…This potentially has large implications for how animals land on different arboreal surfaces following a fall or jump. Our results are a first step towards developing an ecomchanical model for landing in arboreal geckos 64 . Additional data are needed, including habitat use, fine-scale surface parameters, and performance on real-world surfaces.…”
Section: Discussionmentioning
confidence: 83%
“…This potentially has large implications for how animals land on different arboreal surfaces following a fall or jump. Our results are a first step towards developing an ecomchanical model for landing in arboreal geckos 64 . Additional data are needed, including habitat use, fine-scale surface parameters, and performance on real-world surfaces.…”
Section: Discussionmentioning
confidence: 83%
“…Despite day geckos having the best clinging performance overall, we found that the ecologically relevant answer to the question, ‘which species has the highest clinging performance?’ depends on which substrates are available in a given habitat. This ‘ecomechanical’ approach is critical for making predictions about species interactions, survival and ultimately fitness (Higham et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…depends on which substrates are available in a given habitat. This 'ecomechanical' approach is critical for making predictions about species interactions, survival and ultimately fitness (Higham et al, 2021).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…This paradigm applies to all neuromotor patterns performed by animals, with the relationship between “behavior” and “performance” considered as distinct features [ 48 ] playing a key role in determining the behavior. Performance is extracted from precise studies of behavioral sequences investigated using various filming techniques (e.g., high-speed 16 mm and video films, high-speed X-ray films), embarked cameras, and diverse embarked sensors (e.g., electromyography, accelerometers and experimental studies [ 49 , 50 , 51 ]). Although largely discussed, fitness is simply defined here as the ability of the surviving organism to produce offspring that then (at least in part) enter the gene flow process in a population, etc.…”
Section: Behavioral Sequences In Functional Morphologymentioning
confidence: 99%